The Application of Multisim Software as a Learning Medium in Analyzing Semiconductor Diodes Components - Susilaningrum, Arbeti; Rubai, Burhan; Sudana, I Made (Journal of Vocational and Career Education, 2022)
This research aimed to determine the effectiveness of using the Multisim 12 software as a learning medium to achieve the student learning outcomes in electronic engineering competency standards. In this research, the researchers used experimental research to determine the effect of a treatment in a learning process. The subject of this research was the Electronic Engineering students of the State Vocational High School 1 of Ampelgading Pemalang. The researcher involved 72 students of class X as the sample. Before data collection, the researchers conducted observations and interviews, followed by the preparation and validation of research instruments. The research instrument validation was determined by expert judgment. After that, it was tested to the students by the pre-test and post-test. In data analysis, the researchers applied the t-test using the SPSS program as a technique to analyze the learning outcomes. The results of this research showed that the Multisim 12 software was effective to be used as a learning media to analyze semiconductor diode components. It was proved by the increase in the student learning outcomes from the analysis results using SPSS. The Regression Coefficient test (t-test) result showed that the t-count of 8.713 was smaller than the t-table of 2.000.